Strengthening everyday peace formation after ethnic cleansing: operationalising a framework in Myanmar's Rohingya conflict. Issue 2 (1st February 2022) - Ware, Anthony; Ware, Vicki-Ann; Kelly, Leanne M.
ABSTRACT: The concept of everyday peace largely draws on research that, to date, has sought more to explain observed social practices than inform peace interventions. This paper presents a case study of an attempt to operationalise the concept into local non-governmental organisation (NGO) programming, seeking to strengthen the formation of everyday peace between Rohingya and Rakhine communities in Myanmar after recent ethnic cleansing. This is believed to be the first attempt to operationalise everyday peace into NGO practice. The programme incorporates everyday peace components into an existing bottom-up development programme based around Freirian conscientisation, seeking to raise critical awareness of eight social practices seen to constitute everyday peace practice: avoidance, watching/reading, ambiguity, shielding, civility, reciprocity, solidarity and compromise. The paper presents and analyses new field data collected two years into implementation, comprising interviews with 15 local NGO staff/facilitators, and 12 focus groups (gender-segregated) with 84 participants from both Rohingya and Rakhine villages. The paper finds evidence of increased utilisation of these social practices and improved inter-village relations, even in the absence of macro-level peace efforts. While no panacea, and not as yet addressing the deep inequalities, injustices and vulnerabilities between Rohingya and Rakhine communities, this paper finds the approach has contributed to peace formation in this context.